Strategic Embedding of Responsible AI: Governance Architecture and Hybrid Human–AI Value Creation - Tomminen, Valtteri; Leppäniemi, Matti; Kemppainen, Tiina; Frank, Lauri (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Artificial intelligence (AI), particularly generative and agentic systems, is increasingly embedded in organizational processes and customer-facing interactions. While responsible AI research emphasizes governance frameworks and ethical considerations, strategic and digital transformation research focuses on performance and innovation outcomes. These perspectives remain insufficiently integrated, and we lack empirical insight into how responsibility becomes structurally embedded within AI-enabled value creation. Drawing on 44 semi-structured interviews with senior professionals, this study develops a conceptual framework explaining how organizations embed responsible AI through (1) strategic AI governance architecture and (2) hybrid human–AI value creation design. The findings show that responsibility is not treated as a compliance layer but enacted as a structural and operational design feature. Governance architectures align AI with strategy and accountability, while hybrid configurations operationalize responsibility through human oversight, controlled autonomy, transparency, and workflow integration. The study contributes by conceptualizing responsible AI as a strategic embedding process that integrates governance and hybrid human–AI design in organizational value creation.